STUDI DESKRIPTIF KINERJA DOSEN DALAM PROSES PEMBELAJARAN DI UNIVERSITAS MUHAMMADIYAH SURAKARTA - Aly, Abdullah (Universitas Muhammadiyah Surakarta, 2016)
Entering the age of 56, UMS still need to make improvements and development inthe learning process. For the sake of improvement and development, this study was conductedin order to map the performance of UMS lecturer in lesson plan, in the implementation oflearning and in the evaluation of learning outcomes. Based on non-experimental descriptivestudy of the survey form, by questionnaire, review of documents, and FGD, the study foundthree important findings. First, UMS lecturer has a good performance in lesson planning. Second,UMS lecturer’s performance in the implementation of the learning process has not beenentirely good, because they are not using a variety of learning methods. Third, UMS lecturer’sperformance in the evaluation of learning outcomes is quite good. By the three findings abovecan be said that the performance of UMS lecturer in the learning process nearly meet the liabilitycomponent required by Law on Teachers and Lecturers in 2005 and has been referred tothe PP 19 on National Education Standards (NES) in 2005.Keywords: Lecturer’s Performance; Law on Teachers and Lecturers; the National Standards;Student Centered Learning (SCL).Abstrak: Memasuki usianya ke-56, UMS masih harus melakukan perbaikan dan pengembangandalam proses pembelajaran. Untuk kepentingan perbaikan dan pengembangan tersebut,studi ini dilakukan dengan tujuan untuk memetakan kinerja dosen UMS dalam prencanaanpembelajaran, kinerja dosen UMS dalam pelaksanaan pembelajaraan, dan kinerja dosen UMSdalam evaluasi hasil pembelajaran. Berdasarkan studi deskriptif non-eksperimental berbentuksurvei, dengan metode angket, telaah dokumen, dan FGD, studi ini menemukan tiga temuanpenting. Pertama, dosen UMS memiliki kinerja yang baik dalam perencanaan pembelajaran.Kedua, kinerja dosen UMS dalam pelaksanaan proses pembelajaran belum sepenuhnya baik,karena belum menggunakan metode pembelajaran yang beragam. Ketiga, kinerja dosen UMSdalam evaluasi hasil pembelajaran cukup baik. Dengan tiga temuan di atas dapat dikatakanbahwa kinerja dosen UMS dalam proses pembelajaran selama ini hampir memenuhi komponenkewajiban yang diminta oleh UU Guru dan Dosen Tahun 2005 dan telah mengacukepada PP No. 19 tentang Standar Nasional Pendidikan (SNP) Tahun 2005.Kata kunci: Kinerja Dosen; UU Guru dan Dosen; Standar Nasional Pendidikan; StudentCentered Learning (SCL).